Clinical Evaluations of Intraoperative Injection of Platelet-Rich Plasma in Arthroscopic Single-Row Rotator Cuff Repair at 2-Year Follow-Up. (17th March 2021) - Li, Ming; Wang, Kan; Zhang, Haojun; Fang, Chaohua; Liu, Hua; Zhang, Yunfeng
Abstract : Background . The clinical evidence is conflicted on whether platelet-rich plasma (PRP) therapies have a positive effect on tendon healing and improved functional outcomes. Purpose . To evaluate the potentials of intraoperative injection PRP on the speed and quality of healing in patients undergoing arthroscopic repair for small to medium rotator cuff tears. Methods . A total of 86 patients scheduled for arthroscopic single-row repair of small to medium rotator cuff tears were assigned to undergo either PRP injection (PRP group) or conventional repair (control group). The PRP group (N = 43 ) consisted of patients who received an intraoperative injection of liquid PRP. The control group (N = 43 ) consisted of patients who did not receive that treatment. The visual analogue scale (VAS) for pain before treatment and at 1, 14 days, 3, 6, and 24 months after surgery were recorded. The clinical outcomes were assessed by the University of California, Los Angeles (UCLA) and Constant scores before treatment and at 3, 6, and 24 months after surgery and magnetic resonance imaging or ultrasound examination at 24 months. Patient satisfaction and retear rate were also assessed. Results . No statistical differences in baseline characteristics such as age, gender, dominant arm, and tear size were observed between the two groups (P > 0.05 ). For the PRP group, the mean operation time was 40.22 minutes, and for the control group, the mean operation time was 36.3 minutes. There was a statistically significant difference (P = 0.036 ). After surgery, all VAS measurements significantly decreased over time until final follow-up in both groups. No significant difference between the 2 groups was found for any VAS pain measurement at any time point except for the VAS at 1 day postoperatively, which was significantly lower in the PRP group (2.39 ± 1.03 ) than that in the control group (3.21 ± 1.85 ) (P = 0.014 ). Analysis of the PRP and control groups demonstrated a statistically significant improvement in UCLA and Constant scores from baseline to the 3-, 6-, and 24-month follow-up assessments (P < 0.05 ). However, no significant intergroup differences were observed in the clinical scores between the three follow-up time points (P > 0.05 ). At the 24-month follow-up, patient satisfaction rates reached 95.65% and 93.48% for the PRP and control groups, respectively. The retear rate of the PRP group (2/43, 4.65%) was lower than that of the control group (6/43, 13.95%). Conclusions . Although the pain at 1 day after surgery and the retear rate in the PRP group were significantly lower than those in the control group, the liquid PRP injection did not promote better clinical outcomes at the 2-year follow-up.